1994
DOI: 10.1111/j.1600-0714.1994.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Glandular odontogenic cyst: analysis of cytokeratin expression and clinicopathological features

Abstract: The glandular odontogenic cyst (GOC) is a rare odontogenic cyst which is still controversial in regard to classification, terminology, and origin. The first Japanese case of GOC is reported. Immunohistochemical examination for expression of cytokeratins and epithelial membrane antigen by monoclonal antibodies suggested that the lining epithelium was of odontogenic origin with metaplastic mucus-laden cells. We have reviewed the literature and compared the clinicopathological findings of the reported case of GOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 28 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…Immunohistochemical studies using cytokeratin-7, 13, 14 and 19 and their positivity strongly support the odontogenic nature of GOC [32]. The identification of osteodentin [27] and negative reaction for EMA [33] in the area of glandular structures suggest that these features are not of glandular origin and support the concept of odontogenic differentiation in GOC.…”
Section: Discussionmentioning
confidence: 71%
“…Immunohistochemical studies using cytokeratin-7, 13, 14 and 19 and their positivity strongly support the odontogenic nature of GOC [32]. The identification of osteodentin [27] and negative reaction for EMA [33] in the area of glandular structures suggest that these features are not of glandular origin and support the concept of odontogenic differentiation in GOC.…”
Section: Discussionmentioning
confidence: 71%
“…[9] The immunohistochemical examination performed by Semba et al . [11] for expression of cytokeratins and epithelial membrane antigen suggested that the lining of the epithelium was of odontogenic origin with metaplastic mucous-laden cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modality for GOC ranging from curettage, enucleation to en bloc , partial ostectomy have been recommended (1, 2, 5–20, 24, 30). In the present series, nine lesions were first treated by conservative treatment, Extirpation with segmental ostectomy of maxilla/partial mandibulectomy were in remaining three cases.…”
Section: Discussionmentioning
confidence: 99%